Basic Concepts of Modern Thought Islamic Religious Education - Befika Fitriya Dewi; Purwanto (al-Afkar, Journal For Islamic Studies, 2025)
Science and technology since the Middle Ages have experienced rapid development. Along with the development of human thought, today many new discoveries have been produced in various fields of human life. Islamic religious education is currently faced with the challenges of modern human life, so it must be directed at the changing needs of modern society. Islamic religious education needs to be designed to answer the challenges of changing times, and construct it so that it is relevant to changes in society. The aim of this research is to describe the basic concepts of modern Islamic religious education thinking. The research method is a qualitative approach with descriptive research type. Data collection was carried out using literature. The data analysis technique is carried out using descriptive analysis, namely using data presentation and drawing conclusions. The results of the paper show that Islamic Religious Education must develop the quality of its education to meet the ever-changing needs of society. Islamic educational institutions must be able to prepare human resources who have the potential to live together in modern society. Renewal of modern thinking is very necessary in the learning process. Technological advances, for example, learning which in fact the teacher as a facilitator requires tools and media to make it happen, so that it becomes the best means of creating a generation that does not lose ties with their own traditions but also does not become intellectually stupid in education.